ANTIMICROBIAL ACTIVITY OF FRACTIONS AND THE EXTRACT FROM GENTIANA ASCLEPIADEA L. UNDERGROUND PARTS WITH MOLECULAR DOCKING ANALYSIS - Jovanović, Miloš; Matejić, Jelena; Kitić, Dušanka; Mihajilov-Krstev, Tatjana; Kitić, Nemanja; Šavikin, Katarina; Milutinović, Milica (Acta medicae Medianae, 2022)
The willow gentian (Gentiana asclepiadea L.) is a valuable source of secoiridoids, C-glycosylated flavones and xanthones used empirically in the treatment of liver and gastrointestinal disorders. The presented study was aimed to evaluate the antimicrobial activity of the aqueous-ethanolic extract of G. asclepiadea underground parts and its petroleum ether, ethyl acetate, butanol, and water fractions. Molecular docking analysis was performed as well. The antimicrobial activity against pathogens related to gastrointestinal disorders was tested by a microdilution method. The ethyl acetate fraction showed the greatest antimicrobial activity. The lowest MIC of 0.78 mg/ml was observed against Bacillus cereus and Staphylococcus aureus, achieved by the petroleum ether and ethyl acetate fractions, respectively. The greatest bactericidal activity (MBC of 0.78 mg/ml), achieved by the ethyl acetate fractions, was recorded against Enterococcus faecalis. The yeast Candida albicans was the most resistant against the fractions and the extract. C-glycosylated flavones isoorientin and isovitexin showed the best binding affinity on Enterococcus faecalis lipoat-protein ligase A as determined by molecular docking analysis. Considering the results of our study, underground parts of G. asclepiadea could be used as a valuable natural source of secondary metabolites with promising antimicrobial activity.
Keywords: Gentiana asclepiadea, antimicrobial activity, extracts, fractions, molecular docking